Partisipasi Generasi Muda dan Dampak Sosialnya Pada Pemilihan Bupati Tahun 2024 di Kecamatan Hutaraja Tinggi Kabupaten Padang Lawas - Ary Ramadany; Hasyimsyah Nasution (Al Mabhats : Jurnal Penelitian Sosial Agama, 2025)
This study aims to analyze the level of youth participation in the 2024 Regent Election in Hutaraja Tinggi District, Padang Lawas Regency, and to identify the factors influencing their involvement in local political processes. The research employed a qualitative approach, utilizing field observations, in-depth interviews, and documentation gathered from young voters, community leaders, and local election organizers. Findings indicate that while youth participation is relatively high, it is uneven across villages. Greater involvement was observed in areas with better access to political information and education, as opposed to regions with limited political socialization. Interviews revealed that politically literate youth were motivated to participate by their desire for social change and regional development. In contrast, some first-time voters remained apathetic or were primarily influenced by family preferences. Social media played a significant role in enhancing political awareness among youth by disseminating information and digital campaign materials; however, it also posed risks of misinformation. Moreover, community leaders and local role models substantially influenced political behavior, particularly in rural areas. The study identified both encouraging and inhibiting factors: political awareness, social media influence, and community support fostered participation, whereas limited political education, apathy, and distrust toward the political system impeded it. The study concludes that increased access to education, information, and social support correlates with greater youth participation, underscoring the need for collaborative efforts among local governments, the election commission, educational institutions, and youth organizations to strengthen continuous political education and build trust in local democratic systems.